2013
DOI: 10.1001/archgenpsychiatry.2012.1023
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical Disconnection in the Orbitofrontal Region Associated With Cortical Thinning in Schizophrenia

Abstract: These results suggest that, in schizophrenia, regional thalamocortical white matter pathology is specifically associated with cortical pathology in regions where fibers connect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 61 publications
(82 reference statements)
6
64
0
1
Order By: Relevance
“…19,20 Our results indicate that this anomaly may be detected early, even in those with subthreshold clinical symptoms for the diagnosis of schizophrenia. Small neurodevelopmental alterations from early life are speculated to cause this, because the development of the thalamocortical connection begins early in the embryonic stage.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…19,20 Our results indicate that this anomaly may be detected early, even in those with subthreshold clinical symptoms for the diagnosis of schizophrenia. Small neurodevelopmental alterations from early life are speculated to cause this, because the development of the thalamocortical connection begins early in the embryonic stage.…”
Section: Discussionmentioning
confidence: 59%
“…Of note here, a number of recent studies in schizophrenia have focused on connectivity between the thalamus and the prefrontal cortex rather than on the thalamus alone. Using diffusion weighted imaging (DWI), these studies report reduced white matter connectivity between the thalamus and the prefrontal cortex, 19,20 which are consistent with the disconnection theory of schizophrenia. 21,22 These findings are further supported by the fact that some of the symptoms in schizophrenia, such as dysfunction in execution, attention and sensory gating, are related to the thalamoprefrontal circuit.…”
Section: Introductionmentioning
confidence: 66%
“…But neurophysiological evidence of impaired temporal coordination of neural activity in the brains of patients has more recently given the theory a neurophysiological basis (Friston, 1999; Friston and Frith, 1995; Lawrie et al, 2002; Scariati et al, 2016; Stephan et al, 2009). Consistent with this hypothesis, functional imaging studies in patients have repeatedly shown that schizophrenia weakens functional coupling in prefrontal networks based on reduced temporal correlations in BOLD signal across brain areas (Kang et al, 2011; Kubota et al, 2013; Lawrie et al, 2002; Mitelman et al, 2005; Mukherjee et al, 2016; Scariati et al, 2016; Tu et al, 2012, 2013). Measurements of brain activity at higher temporal resolution using electroencephalograms (EEG) and magnetoencephalography (MEG) have shown reduced synchrony in gamma band during task performance (Dale et al, 2016; Uhlhaas and Singer, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…Imaging data during this phase showed global changes in neural connectivity (Friedman et al, 2008). Furthermore, both white and gray matters, especially cortical thickness have been shown altered in these patients, whose degree of changes may be correlated with their functional status (Kubota et al, 2013; Sasamoto et al, 2014; Ubukata et al, 2013). These patients may show a lack of motivation as well as difficulty in activating task-relevant networks.…”
Section: Neurobiological Basis For Cognitive Impairments In Schizomentioning
confidence: 94%